2019
DOI: 10.20319/pijtel.2019.31.245257
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Communicative Language Teaching Method in the Libyan Class at a Uk University: Lesson Plan, Rationale and Evaluation

Abstract: This study provides a rationale for a lesson plan about the implementation of the communicative language teaching method (CLT) in the Libyan class at a UK University. The aim of the lesson plan is to develop learner"s reading skills and to develop oral fluency. The lesson is aimed for adult learners at pre-intermediate level who are studying English for general purposes. The topic of the lesson is about the types of food that are eaten around the world and the geographical, economical, and lifestyle reasons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Clear instruction was necessary, but modeling just one time was not enough, two or three times with different examples was more appropriate because repetition was the key (Kwon, 2017). Another strategy that worked well was to give students enough time to develop their activities but always letting them know that they had a limit of time; this let them realize that they had to work with a certain pace because every activity had an time limit (Algwil, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Clear instruction was necessary, but modeling just one time was not enough, two or three times with different examples was more appropriate because repetition was the key (Kwon, 2017). Another strategy that worked well was to give students enough time to develop their activities but always letting them know that they had a limit of time; this let them realize that they had to work with a certain pace because every activity had an time limit (Algwil, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, However, the study by Laurillard (2009) and Stahl, Koschman and Sutter (2006) considered collaborative-learning as a more students-centered learning while solving a problem. While the study by Algwil (2019) considered the role of group-work in providing easier learning in communicative language learning, the result of the study by Amini-Philips (2019) showed that students are not willing to collaboratively working with each other and it was assumed due to the competition among them. Nowadays, collaborative-learning are not limited to the classroom thanks to development of new technologies.…”
Section: Introductionmentioning
confidence: 99%